2022
DOI: 10.1038/s41612-022-00296-w
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Pacific sector sea ice loss on the sudden stratospheric warming characteristics

Abstract: The atmospheric response to Arctic sea ice loss remains a subject of much debate. Most studies have focused on the sea ice retreat in the Barents-Kara Seas and its troposphere-stratosphere influence. Here, we investigate the impact of large sea ice loss over the Chukchi-Bering Seas on the sudden stratospheric warming (SSW) phenomenon during the easterly phase of the Quasi-Biennial Oscillation through idealized large-ensemble experiments based on a global atmospheric model with a well-resolved stratosphere. Alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…It is important to note that our simulations were based on idealized test cases, and although an unusual performance of the FV core was evident, the real‐world applicability of these results is uncertain. In real general circulation model (GCM) simulations, significant contributions may come from physics parameterizations such as gravity wave drag (Marsh et al., 2013) and the sea‐ice effect (Zhang et al., 2022). To fully understand the impact of the dynamical core on real‐world SSWs, further research that includes various large‐scale evaluations and long‐duration simulations is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that our simulations were based on idealized test cases, and although an unusual performance of the FV core was evident, the real‐world applicability of these results is uncertain. In real general circulation model (GCM) simulations, significant contributions may come from physics parameterizations such as gravity wave drag (Marsh et al., 2013) and the sea‐ice effect (Zhang et al., 2022). To fully understand the impact of the dynamical core on real‐world SSWs, further research that includes various large‐scale evaluations and long‐duration simulations is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…The subseasonal “stretched” stratospheric polar vortex variations modified by abnormal states of Arctic sea ice and Eurasian snow cover is linked with the recent winter extreme cold across parts of Asia and North America (Cohen et al., 2021). It was also shown that SICs losses in the North Pacific could increases the SSW duration and intensity, and then enhance cold air outbreaks over the continents (J. R. Zhang et al., 2022). Thus, how spring stratospheric polar vortex subseasonal modes influence SAT over EC and how their linkage is modulated by Arctic SIC variations are of importance to address in the future.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…The SSW‐induced effects extend well beyond the polar stratosphere and their impacts are well detected from oceans to the ionosphere (Goncharenko et al., 2010; Liu et al., 2019; Zhang et al., 2022). Some studies have shown that even as a predictor of several tropospheric weather events, stratospheric harbingers may be used (Baldwin & Dunkerton, 2001; Julian & Labitzke, 1965; Quiroz, 1977).…”
Section: Introductionmentioning
confidence: 99%